ANALISIS LAPORAN KEUANGAN PADA CV. CITRASAN PASIR PENGARAIAN - Nuryanto, Asep (Jurnal Mahasiswa Prodi SI Manajemen, 2013)
This research was did in the CV. Citrasan Pasir Pengaraian, the objective of the research is to find out the form of financial reports that used of CV. Citrasan Pasir Pengaraian and The condition of financial CV Citrasan Pasir Pengaraian that we can saw from financial reports 2011-2012.The informant to get the data financial reports is CV. Citrasan Pasir Pengaraian and workers. To analysis of the data the writer used Horizontal technique. It is to compare financial reports in several periods. The writer uses the descriptive qualitative method to describe the general form from the research to tabulation form.CV. citrasan Pasir Pengaraian is a company that is sell and buy Electronics Equipments and in the area of service Warnet. CV. Citrasan still uses the simple financial reports where are the financial reports consisting of balance sheet and profit and loss statement.From the comparison of analysis of balance sheet CV. Citrasan Pasir Pengaraian 2011-2012 the writer get the data of CV. Citrasan Pasir Pengaraian Financial is good, where are the elements of balance sheet increasing from 2011. From Ratio Analysis at balance sheet and profit and loss statement CV. Citrasan Pasir Pengaraian 2011-2012 the result is good so that CV. Citrasan Pasir Pengaraian will develop and rise.In order that nothing wrong in saw the condition of company financial, the writer give the suggestion for owner of company and workers make a complete financial report so that from the complete financial report we can more understand and we can know where frailty of company is.